Research Advances in Recycling Technologies for Valuable Components from Spent Lithium-Ion Batteries - Bakera, María; Bustamante, Pablo V. (Journal of Green Energy and Environmental Engineering, 2026)
With the rapid expansion of the new energy industry, lithium-ion batteries have witnessed explosive growth in production and deployment, driven by broadening applications in electric vehicles, consumer electronics, and grid-scale energy storage. Consequently, the volume of retired batteries is increasing annually. Spent lithium-ion batteries contain high concentrations of strategic metals—notably nickel, cobalt, and lithium—that hold substantial economic value. Inadequate recycling not only results in significant resource depletion but also triggers severe environmental risks, including soil and groundwater contamination from heavy metal leaching, threatening both ecological systems and human health. Current recycling technologies for spent lithium-ion batteries are broadly classified into three categories: physical methods, chemical methods, and biological methods. This review analyzes each technology based on its fundamental operating principles, systematically evaluating key performance indicators including metal recovery efficiency, economic feasibility, and environmental footprint, while discussing their respective technical strengths and application limitations. To address existing bottlenecks, we propose an integrated strategy: employing intelligent sorting technologies for pre-separation and enrichment of compositionally uniform fractions, followed by conventional physical and chemical recycling processes. Future recycling systems are expected to evolve toward intelligent, green, and short-process paradigms, minimizing energy consumption and environmental impact across the entire recovery chain.